Olfactory sensitivity of the gilthead seabream (Sparus aurata) to conspecific body fluids: potential sources of pheromones - Barata, Eduardo N. (2008)
The potential for intraspecific chemical communication in the gilt-head seabream (a marine perciform) was investigated by assessing the olfactory sensitivity to conspecific body-fluids (water occupied by conspecifics, intestinal fluid, urine, semen, egg fluid) by multiunit electrophysiological recording from the olfactory nerve. The olfactory system was responsive to water previously occupied by conspecifics, and the active compound(s) could be extracted by solid-phase extraction. The olfactory system was extremely sensitive to body fluids of sexually mature conspecifics: thresholds of detection were 1: 107: 4 (intestinal fluid), 1: 106: 1 (gametes), and 1: 104: 2 (urine). The olfactory system was also sensitive to amino acids with thresholds of detection from 10(-8.1) M (L-leucine) to 10(-6.1) M (L-phenylalanine). However, a range of other known fish odorants (steroids, bile acids, and prostaglandins) failed to evoke significant responses. Given the high olfactory sensitivity to intestinal fluid and the low urine release rates of marine compared with freshwater fish, we suggest that chemical communication is likely to be mediated via compounds present in the intestinal fluid rather than urine. Furthermore, the types of chemicals involved are likely to be different from those of freshwater fish. Their exact chemical identity and biological roles remain to be established.